Because I said so! : the truth behind the myths, tales and warnings every generation passes down to its kids - Jennings, Ken, 1974- (Scribner, 2012)
"New York Times" bestselling author and all-time "Jeopardy!" champion Ken Jennings delivers a characteristically engaging and surprisingly useful new book, revealing the truth behind all the terrible things our parents used to warn us about.